1979
DOI: 10.1055/s-0028-1098324
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Snare Polypectomy – A Safer Technique for Electrocoagulation of Large Polyp Stalks

Abstract: Conventional colonoscopic snare polypectomy for large polyps with stalk diameter of 1.5 cm or more carries a significant risk of haemorrhage after transection, probably due to "leak currents". The use of a return-electrode applied to the base of the polyp after snaring instead of the conventional patient-plate permits bi-polar polypectomy which is both safer and more efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…This device theoretically minimizes the depth of the burn and thus the degree of tissue destruction. Williams and de Peyer [16] were the first to report use of the bipolar snare for safer endoscopic resection. However, because this technique was complicated and required a two-channel scope, it was not widely used thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This device theoretically minimizes the depth of the burn and thus the degree of tissue destruction. Williams and de Peyer [16] were the first to report use of the bipolar snare for safer endoscopic resection. However, because this technique was complicated and required a two-channel scope, it was not widely used thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Among the devices used for removal, the bipolar snare is an option. Use of the bipolar snare as a safer technique for polypectomy was first reported by Williams and de Peyer [16] in 1979. Tucker et al [17] evaluated the energy required and the tissue damage created by the monopolar and bipolar snares in a canine model.…”
mentioning
confidence: 99%
“…Snare polypectomy was performed in 8 patients (13 polyps, of which 5 were at least 2 cm in diameter). 25 The polypectomies in our series were considered technically easy for an endoscopist with experience of more than 1000 adult polypectomies, since the majority of the polyps were juvenile with characteristically thin stalks.…”
Section: Resultsmentioning
confidence: 91%
“…One way to reduce complications during therapeutic endoscopy is the use of a bipolar instrument. This device theoretically minimizes the depth of burning and degree of tissue destruction [21,22]. Saraya et al reported an incidence of perforation as low as 0.08% for endoscopic resection with a bipolar snare.…”
Section: Discussionmentioning
confidence: 99%